A Study on the Identity Crisis and Lack of Academic Motivation Among Korean Student-Athletes - Park, Sanghui (Technium Social Sciences Journal, 2025)
The purpose of this study is to examine the imbalance between academic and athletic performance among South Korean student-athletes, focusing on the systemic, cultural and institutional factors that affect the negative association between academics and athletics. By comparing NCAA policies and American student-athletes, this paper investigates how South Korea’s authoritarian training culture and lack of academic support prioritize athletic performance over education. The early start to intensive live-in training camps, and the complicity of teachers and coaches reinforce the identity of young athletes as competitors rather than students, leading to disengagement from academics and limited long-term career prospects. Although the Korean University Sport Federation (KUSF) and the Ministry of Education has implemented policies such as minimum grade and attendance requirements, these measures remain insufficient without broader cultural change and stronger academic support systems. Through a comparative lens with U.S. practices, this paper argues that restoring the dual identity of student-athletes requires collaborative reforms across schools, coaches, and policymakers. Ultimately, embedding academic accountability within Korea’s sports system is essential for empowering athletes to succeed both on and off the field.